Mast cell activation triggered by SARS-CoV-2 causes inflammation in brain microvascular endothelial cells and microglia - Wu, Meng-Li; Xie, Chengzuo; Li, Xin; Sun, Jing; Zhao, Jincun; Wang, Jian-Hua (Frontiers in Cellular and Infection Microbiology, 2024)
SARS-CoV-2-induced excessive inflammation in brain leads to damage of blood-brain barrier, hypoxic-ischemic injury, and neuron degeneration. The production of inflammatory cytokines by brain microvascular endothelial cells and microglia are reported to be critically associated with the brain pathology of COVID-19 patients. However, the cellular mechanisms for SARS-CoV-2inducing activation of brain cells and the subsequent neuroinflammation remain to be fully delineated. Our research, along with others', have recently demonstrated that SARS-CoV-2-induced accumulation and activation of mast cells (MCs) in mouse lung could further induce inflammatory cytokines and consequent lung damages. Intracerebral MCs activation and their crosstalk with other brain cells could induce neuroinflammation that play important roles in neurodegenerative diseases including virus-induced neuropathophysiology. In this study, we investigated the role of MC activation in SARS-CoV-2-induced neuroinflammation. We found that: (1) SARS-CoV-2 infection triggered MC accumulation in the cerebrovascular region of mice; (2) spike/RBD (Receptor Binding Domain) protein-triggered MC activation induced inflammatory factors in human brain microvascular endothelial cells and microglia; (3) MC activation and degranulation destroyed the tight junction proteins in brain microvascular endothelial cells, and induced the activation and proliferation of microglia. These findings reveal a cellular mechanism of SARS-CoV-2-induced neuroinflammation.